Can someone walk me through this?

the answer should be $\displaystyle \frac{a(1-r^n)}{1-r}+\frac{dr}{(1-r)^2}[1+nr^{n-1}-(n-1)r^n]$

Many thanks.

Printable View

- Dec 5th 2011, 12:09 PMBabyMiloSum of series problem #2
Can someone walk me through this?

the answer should be $\displaystyle \frac{a(1-r^n)}{1-r}+\frac{dr}{(1-r)^2}[1+nr^{n-1}-(n-1)r^n]$

Many thanks. - Dec 5th 2011, 01:20 PMwnvlRe: Sum of series problem #2
$\displaystyle =a \sum_{k=0}^{n-1}r^{k}+r\cdot d\cdot \frac{\mathrm{d} }{\mathrm{d} r}\sum_{k=0}^{n-1}r^{k}$

$\displaystyle =a\frac{r^n-1}{r-1}+dr\frac{\mathrm{d} }{\mathrm{d} r}\sum_{k=0}^{n-1}\frac{r^n-1}{r-1}$